2019
DOI: 10.1103/physrevfluids.4.014801
|View full text |Cite
|
Sign up to set email alerts
|

Classification of internal solitary wave breaking over a slope

Abstract: Breaking of shoaling internal solitary waves (ISWs) is important for mixing and mass transport processes in oceans and lakes. For ISWs in a two-layer stratified fluid, previous studies identified four breaker types: surging, plunging, collapsing, and fission. The latest classification of these breaker types is based on the wave slope S w and the bottom slope S; however, this classification was found to be unsatisfactory in delineating collapsing and plunging breakers. The present study proposes a new classific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 77 publications
6
27
0
Order By: Relevance
“…Higher temporal resolution velocity observations would allow more detailed analysis. The wave form was similar to the result of a collapsing wave of depression as modeled by Nakayama et al (2019) and Arthur and Fringer (2014). The largest overturns were found at the trailing‐face of this wave.…”
Section: Characterizing the Instabilities Of Nliw Of Elevationsupporting
confidence: 79%
“…Higher temporal resolution velocity observations would allow more detailed analysis. The wave form was similar to the result of a collapsing wave of depression as modeled by Nakayama et al (2019) and Arthur and Fringer (2014). The largest overturns were found at the trailing‐face of this wave.…”
Section: Characterizing the Instabilities Of Nliw Of Elevationsupporting
confidence: 79%
“…Many of the above flow features are also observed with shoaling mode-1 waves, where several extensive laboratory and numerical model studies have been undertaken (see, for example, Boegman et al (2005); Aghsaee et al (2010); Sutherland et al (2013); Nakayama et al (2019) and references therein). These studies have been successful in not only delineating the different processes determining the shoaling behaviour of mode-1 ISWs for different combinations of boundary slope s and wave slope s w (= a/L w ) but also characterising and classifying the shoaling regimes in terms of these parameters.…”
Section: Introductionmentioning
confidence: 97%
“…Reflection (with no breaking) is seen for very steep slopes. For intermediate (moderate to steep) slopes, several different types (surging, collapsing, collapsing plunging, plunging) of wave breaking occur, with the breaking regimes being classified conveniently in terms of s, s w and the relative values of the time scales characterising the individual wave breaking processes (Aghsaee et al 2010;Nakayama et al 2019). Sutherland et al (2013) demonstrate that shoaling-induced breaking regimes of mode-1 ISWs can be classified successfully in terms of the bed slope s and an internal Iribarren † number Ir = s/(s w ) 1/2 , subject to careful definition of the length scale L w .…”
Section: Introductionmentioning
confidence: 99%
“…In field observations, Pineda (1994), Inall (2009) and Bourgault et al (2014) show that internal waves induce long-term mass transport due to breaking over a sill or a bottom slope and have an important influence on the environment in stratified fluids. In numerical calculations it has been shown that the breaking of internal solitary waves can be categorized using the wave slope, bottom slope and an internal solitary wave Reynolds number (Aghsaee, Boegman & Lamb 2010;Nakayama et al 2012Nakayama et al , 2019b. Additionally, the occurrence of long-term mass transport by internal waves has been observed in laboratory experiments (Nakayama & Imberger 2010;Nakayama et al 2012;Sutherland, Barrett & Ivey 2013).…”
Section: Introductionmentioning
confidence: 99%